A synthesised approach for antitrust interference in the exercise of SEPs: comparative perspectives from China, USA and EU. (2017) - Wang, Zhongmei
Recent proceedings involving SEPs in many regions and countries raised the same question: when would it be appropriate for antitrust interference in the exercise of patent propriety? According to current practices worldwide, there are two lines to distinguish between the normal excise of IP rights and the abuse of dominance: one is a procedural line which requires negotiation with good faith; the other is a substantive line which requires all the licensing conditions shall be fair, reasonable and non-discriminatory. Any exercise of SEPs including seeking an injunction or charging a loyalty rate is supposed not to surpass the two lines. Otherwise it would provide bases for antitrust interference. However, although the framework is similar, the concrete approaches adopted by different jurisdictions are varied to some extent. That is why here a synthesised approach is proposed and recommended.